2019
DOI: 10.1071/an18301
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of residual feed intake and pre-natal diet on reproductive potential of bulls

Abstract: Our objective was to determine effects of genetic potential for residual feed intake (RFI) and pre-natal diet on post-natal growth and reproductive development of bulls. Twenty-five bull calves with a divergent potential for RFI were produced by mating purebred Angus heifers (60) categorised as high or low RFI and inseminated with semen from high or low RFI bulls. From 30 to 150 days of gestation, half the heifers (balanced for RFI across treatments) in each RFI category were fed to gain 0.7 or 0.5 kg/day (~10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Twenty-six purebred Angus bulls raised on the Roy Berg, University of Alberta Kinsella Ranch (Kinsella, AB, Canada), were used in this study. After weaning, the bulls were fed and managed according to industry standards for feedlot production of finished cattle in Alberta until they reached approximately 17 months of age [68]. The bulls were then slaughtered at the Agriculture and Agri-Food Canada (AAFC)-Lacombe Research Centre abattoir over a period of four days to collect the target tissues [68].…”
Section: Animal Selectionmentioning
confidence: 99%
“…Twenty-six purebred Angus bulls raised on the Roy Berg, University of Alberta Kinsella Ranch (Kinsella, AB, Canada), were used in this study. After weaning, the bulls were fed and managed according to industry standards for feedlot production of finished cattle in Alberta until they reached approximately 17 months of age [68]. The bulls were then slaughtered at the Agriculture and Agri-Food Canada (AAFC)-Lacombe Research Centre abattoir over a period of four days to collect the target tissues [68].…”
Section: Animal Selectionmentioning
confidence: 99%
“…As well, a greater number of progeny per sire was seen for LRFI bulls in a multi-sire natural mating experiment ( Wang et al, 2012 ). In contrast, other studies found that LRFI bulls had a smaller scrotal circumference ( Johnson et al, 2019 ), decreased sperm motility ( Wang et al, 2012 ; Awda et al, 2013 ; Johnson et al, 2019 ), decreased progressive sperm motility, increased abundance of tail abnormalities, and delayed sexual maturity ( Fontoura et al, 2016 ; Montanholi et al, 2016 ). Moreover, when RFI was adjusted for backfat thickness, LRFIfat bulls displayed lower sperm motility, decreased progressive sperm motility, as well as a smaller scrotal circumference ( Awda et al, 2013 ).…”
Section: Introductionmentioning
confidence: 79%
“…Because no net increase in muscle fibre numbers occurs after birth, nutrient insults during early gestation may change nutrient partitioning to essential organs rather than skeletal muscle ( Greenwood et al, 2000 ; Zhu et al, 2006 ; Long et al, 2009 ; Du et al, 2010 ; Funston et al, 2010 ; Du et al, 2011 ). Several studies have shown that calves born from dams that were nutritionally restricted during early-to mid-gestation and then re-alimented before parturition had similar ratios of weight gain to feed intake ( Long et al, 2009 ; Long et al, 2012 ; Johnson et al, 2019 ). However, there is some evidence for increased weight gain between 10 and 16 months of age compared to their normally fed control groups ( Johnson et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations